The Fluid Mechanics of Transcatheter Heart Valve Leaflet Thrombosis in the Neosinus. Issue 17 (24th October 2017) - Midha, Prem A.; Raghav, Vrishank; Sharma, Rahul; Condado, Jose F.; Okafor, Ikechukwu U.; Rami, Tanya; Kumar, Gautam; Thourani, Vinod H.; Jilaihawi, Hasan; Babaliaros, Vasilis; Makkar, Raj R.; Yoganathan, Ajit P.
Abstract : Background: Transcatheter heart valve (THV) thrombosis has been increasingly reported. In these studies, thrombus quantification has been based on a 2-dimensional assessment of a 3-dimensional phenomenon. Methods: Postprocedural, 4-dimensional, volume-rendered CT data of patients with CoreValve, Evolut R, and SAPIEN 3 transcatheter aortic valve replacement enrolled in the RESOLVE study (Assessment of Transcatheter and Surgical Aortic Bioprosthetic Valve Dysfunction With Multimodality Imaging and Its Treatment with Anticoagulation) were included in this analysis. Patients on anticoagulation were excluded. SAPIEN 3 and CoreValve/Evolut R patients with and without hypoattenuated leaflet thickening were included to study differences between groups. Patients were classified as having THV thrombosis if there was any evidence of hypoattenuated leaflet thickening. Anatomic and THV deployment geometries were analyzed, and thrombus volumes were computed through manual 3-dimensional reconstruction. We aimed to identify and evaluate risk factors that contribute to THV thrombosis through the combination of retrospective clinical data analysis and in vitro imaging in the space between the native and THV leaflets (neosinus). Results: SAPIEN 3 valves with leaflet thrombosis were on average 10% further expanded (by diameter) than those without (95.5±5.2% versus 85.4±3.9%; P <0.001). However, this relationship was not evident with the CoreValve/Evolut R. In CoreValve/Evolut Rs with thrombosis, the thrombus volume increased linearly with implant depth ( R 2 =0.7, P <0.001). This finding was not seen in the SAPIEN 3. The in vitro analysis showed that a supraannular THV deployment resulted in a nearly 7-fold decrease in stagnation zone size (velocities <0.1 m/s) when compared with an intraannular deployment. In addition, the in vitro model indicated that the size of the stagnation zone increased as cardiac output decreased. Conclusions: Although transcatheter aortic valve replacement thrombosis is a multifactorial process involving foreign materials, patient-specific blood chemistry, and complex flow patterns, our study indicates that deployed THV geometry may have implications on the occurrence of thrombosis. In addition, a supraannular neosinus may reduce thrombosis risk because of reduced flow stasis. Although additional prospective studies are needed to further develop strategies for minimizing thrombus burden, these results may help identify patients at higher thrombosis risk and aid in the development of next-generation devices with reduced thrombosis risk. Abstract : Supplemental Digital Content is available in the text.